Schimbarea profilului demografic și ocupațional al populației rurale: 1990-2009 - Mihalache, Florentin Flavius (Calitatea Vieții, 2010)
This paper explores the demographic and occupational changes in rural Romania, during 1990–2009. In the last 20 years, rural population decreased by more than 1 million people. Birth rates and fertility rates were considerably reduced, while external migration exploded. Under these circumstances, the aging process and the depopulation of some areas have become central issues for rural space. On the other hand, the effects of economic transition on employment of rural population were dramatic: the number of people employed in agriculture has increased while the number of employees has decreased dramatically. Thus, subsistence farming and self – consumption have become widespread in rural areas.